My body - Jacobs, Martina; Jacobs, Sophia; Duncan, Myra.; Cherbourg State School (Qld.). Guluin Pre-Prep Class; Smith Family (Charity); AMP Foundation; Zig Zag Foundation (Murgon, Qld. : Cherbourg State School, 2008)
Photographs of pre-prep students with the names of body parts; students from pre-prep to year 7 created a variety of books as pasrt of the 'Strong and Smart' early years literacy project.
"Special thanks to all the Community Elders in Cherbourg who have given their support and advice for this project."--Cover verso.
"This book is part of a `Strong and smart' early years literacy project."--Back cover.
For children.
"An Early Years Literacy Project funded by The Smith Family with the generous support of the AMP Foundation and the Zig Zag Foundation"--Cover verso.
Keywords: Human body -- Pictorial works -- Juvenile literature; Human anatomy -- Pictorial works -- Juvenile literature; Children, Aboriginal Australian -- Queensland -- Cherboug Aboriginal Community -- Juvenile literature; Education - Teaching - Materials; Education - Language - English - Readers and primers; Language - Vocabulary - Body parts and functions; Education - Language - Literacy; Cherbourg / Barambah (SE Qld SG56-10); Australian